Alcohol consumption upon direct-acting antiviral therapy for hepatitis C among persons with human immunodeficiency virus in the United States. (1st December 2022) - Chen, Po-Hung; Yenokyan, Karine; Fojo, Anthony T.; Hutton, Heidi E.; Lesko, Catherine R.; McCaul, Mary E.; Yang, Cui; Cachay, Edward R.; Crane, Heidi M.; Jacobson, Jeffrey M.; Kim, H. Nina; Kitahata, Mari M.; et al.
Abstract: Background: Direct-acting antivirals (DAA) are highly effective against hepatitis C virus (HCV) infection among persons with human immunodeficiency virus (PWH). However, alcohol use post-DAA treatment poses a continued threat to the liver. Whether the focus on liver health alone during HCV treatment can impact alcohol consumption is unclear. Therefore, we examined the change in alcohol use among HCV-coinfected PWH who received DAA therapy by non-addiction medical providers. Methods: In our longitudinal clinical cohort study, we identified HCV-coinfected PWH who received interferon-free DAA therapy between January 2014 and June 2019 in the Centers for AIDS Research Network of Integrated Clinical Systems. The Alcohol Use Disorders Identification Test—Consumption (AUDIT-C) was the alcohol screening instrument. We used mixed-effects logistic regression models to estimate the longitudinal change in alcohol use upon DAA therapy. Results: Among 738 HCV-coinfected PWH, 339 (46 %) reported any alcohol use at the end of HCV treatment, including 113 (15 %) with high-risk use (i.e., AUDIT-C ≥3 for women, ≥4 for men). Concurrently, 280 (38 %) PWH noted active drug use, and 357 (48 %) were currently smoking. We observed no changes in the odds of any alcohol or high-risk alcohol use over time with DAA therapy. Findings were similar in the PWH subgroup with a history of alcohol use before DAA treatment. Conclusions: For PWH with HCV, alcohol use did not change following interferon-free DAA treatment by non-addiction medical providers. Thus, clinicians should consider integrating targeted alcohol use interventions into HCV care to motivate reduced alcohol consumption and safeguard future liver health. Highlights: After treating HCV, unhealthy alcohol use risks further liver disease progression. Knowing one's own HCV status elicits self-awareness for needing to reduce alcohol. Alcohol use among PWH did not change after DAA therapy by non-addiction clinicians. Alcohol use also did not change in the subgroup with a known history of drinking. Co-delivering alcohol interventions alongside standard HCV care may be needed.